Assessment of the Role of Pharmacists in Preventing Medication Errors in Hospital Settings - Gupta, Yash; Kumar, Neeraj; Shukla, Amrita; Rai, Vishal (Journal for Research in Applied Sciences and Biotechnology, 2023)
Medication errors can have serious consequences for patients in hospital settings. As medication experts, pharmacists play a critical role in preventing medication errors. This literature review examines the roles of pharmacists in preventing medication errors in hospital settings. The review identified several roles of pharmacists in preventing medication errors, including medication order review, medication reconciliation, providing drug information and education, and participation in interdisciplinary teams. The review also identified barriers to pharmacist involvement in preventing medication errors, such as limited access to patient information and limited communication with other healthcare professionals. Overall, the literature suggests that pharmacists can play a crucial role in preventing medication errors in hospital settings and that efforts should be made to overcome the barriers to their involvement.